Ionic liquid ultrasound-assisted extraction (IL-UAE) for duck feather keratin and in silico evaluation as a potential procollagen n-endopeptidase inhibitor - Sianita, Maria Monica; Kusumawati, Nita; Asri, Mahanani Tri; Dzulkarnain, Shod Abdurrachman; Al Hafidl, Achmad Naufal; Kahfi, Ashabul; Nabila, Mutiara Azfa; Setiawan, Ferdiansyah; Isyrak, Luthfiyah; Rahmawati, Khofifatul (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
This research aims to optimize keratin extraction from duck feathers using an eco-friendly ionic liquid-ultrasound-assisted extraction (IL-UAE) method and evaluate its potential applications in tissue engineering. It investigated the effects of deposition pH (1-6), ultrasonication temperature (40-60°C), and time (60-180 min) on extraction yield and physicochemical properties. The results demonstrated the optimal extraction conditions at pH 3, 40°C, and 60 minutes, yielding 82% keratin with a 0.50 mg/mL concentration, while the lowest yield production was found at pH 6 (33%, 0.20 mg/mL). Meanwhile, characterization via FTIR confirmed predominant ?-sheet structures with characteristic peaks at 3250-3300 cm?¹ (N-H/O-H stretching) and 1700-1500 cm?¹ (C=O stretching). SDS-PAGE revealed pure keratin bands (10-15 kDa), while SEM showed layered, porous morphology suitable for biomaterial applications. Thermogravimetric analysis, furthermore, identified three degradation stages occurred at 0-200°C (3.05% loss), 200-400°C (39.37% loss), and 400-700°C (31.13% loss). Amino acid profiling revealed high L-cystine content (153,064.90-156,926.33 mg/kg) with the significant amounts of glycine (63,958.25-64,064.73 mg/kg), L-proline (77,631.16-77,717.42 mg/kg), and L-leucine (59,111.43-59,198.60 mg/kg). In silico molecular docking studies identified leucine as a promising procollagen N-endopeptidase inhibitor (binding energy -5.0 kcal/mol), which controlled the collagen-breaking and forming process. This ability makes keratin potential to be developed as a scaffold for bone tissue regeneration in medical industry.